IDENTIFIKASI LIMA TAHUN PASCA PENGUKUHAN BATIK OLEH UNESCO TERHADAP PERKEMBANGAN IKM BATIK DI KOTA PEKALONGAN (Studi Kasus di kampung Batik kauman dan Kampung Batik Pesindon) - Wenti Ayu Sunarjo; Mutadin Mutadin; Maghfiroh Maghfiroh (JURNAL LITBANG KOTA PEKALONGAN, 2014)
This research entitle “Identification of Post-Inauguration Five years Batik by UNESCO Against IKM Developments in Pekalongan Batik City” has the aim to testing corelation among variables to reality faced are the poor track record or clear documentation related economic development in Village Batik Kauman and Tourism Village Batik Pesindon post-inaugural Batik Indonesia by UNESCO. This research includes the quantitative descriptive research that use the descriptive statistic analysis method. The population is all of ceaftman at village batik kauman and tourism village batik pesindon, Pekalongan city. The number of samples was determined by the method of interview on some IKM contained in the research object, especially IKM who take charge of the village community kauman batik and batik pesindon tourist village. The result of this research show thah that have affected the development of SMEs batik in Pekalongan city, especially in villages kauman batik and batik pesindon tourist village there are three variables, namely, the number of SMEs, the amount of labor and production capacity. Where these three things are very influential on the turnover obtained. Keywords : five years after the inauguration of batik by UNESCO, the development of batik IKM